2002
DOI: 10.1128/cdli.9.5.1049-1056.2002
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cytokine Production and Its Effect on Induced Production

Abstract: Cytokines regulate cellular immune activity and are produced by a variety of cells, especially lymphocytes, monocytes, and macrophages. Multiparameter flow cytometry is often used to examine cell-specific cytokine production after in vitro phorbol 12-myristate 13-acetate and ionomycin induction, with brefeldin A or other agents added to inhibit protein secretion. Spontaneous ex vivo production reportedly rarely occurs. We examined the spontaneous production of interleukin 2 (IL-2), IL-4, IL-6, IL-8, IL-10, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 24 publications
2
31
1
1
Order By: Relevance
“…The spontaneous production of cytokines by unstimulated PBMCs has been described previously in healthy persons living in developing countries where there is high prevalence of human immunodeficiency virus, as well as mycobacterial, malarial, and other parasitic infections (44)(45)(46)(47). Although IL-6 has been commonly associated with severe malaria (48)(49)(50), our study indicates the contrary, i.e., we found that significantly higher levels of this cytokine were present in animals that resisted severe malaria.…”
Section: Figcontrasting
confidence: 56%
“…The spontaneous production of cytokines by unstimulated PBMCs has been described previously in healthy persons living in developing countries where there is high prevalence of human immunodeficiency virus, as well as mycobacterial, malarial, and other parasitic infections (44)(45)(46)(47). Although IL-6 has been commonly associated with severe malaria (48)(49)(50), our study indicates the contrary, i.e., we found that significantly higher levels of this cytokine were present in animals that resisted severe malaria.…”
Section: Figcontrasting
confidence: 56%
“…2D). Spontaneous TNF production has been described in humans as well (40) and thus requires proper attention during the identification of recall T-cell responses responsible for vaccine-induced protection.…”
Section: Cd4mentioning
confidence: 99%
“…28 In addition, most cytokine-secreting cells also produce TNFa 13,[29][30][31][32][33] that makes it a good candidate as a universal marker to be used for the identification of cytokine-secreting cells. Up till now, the most commonly used cell surface marker to detect recently activated lymphocytes and other immune cells has been CD69.…”
Section: Discussionmentioning
confidence: 99%